Coordination structure and extraction behavior of a silver ion with N-substituted-9-aza-3, 6, 12, 15-tetrathiaheptadecanes: significant effect of Ph–C–N framework on the extractability. Issue 31 (20th July 2016) - Iwatsuki, Satoshi; Ichiyama, Atsushi; Tanooka, Syogo; Toyama, Mari; Katagiri, Kosuke; Kawahata, Masatoshi; Yamaguchi, Kentaro; Danjo, Hiroshi; Chayama, Kenji
Abstract : The N -substituent having a Ph–C–N framework on monoazatetrathioethers significantly enhanced the Ag(i ) extractability due to its "hydrophobic cover" effect. Abstract : N -Substituted-9-aza-3, 6, 12, 15-tetrathiaheptadecanes having Ph–C–N frameworks ( N -R-ATH ; R = benzyl ( N -Bn-ATH ), 4-nitrobenzyl ( N -NO2 Bn-ATH ), and diphenylmethyl ( N -Ph2 CH-ATH )) were synthesized, and their Ag(i ) complexes were structurally characterized. X-Ray crystal structure analyses of [Ag( N -R-ATH )](BF4 ) (R = Bn and Ph2 CH) revealed monomeric tetra- S -coordinated complex cation structures without the N -coordination, and a benzene ring of the N -R group covered over the amine nitrogen atom. The precise extraction analyses of a Ag(i ) ion with ATH derivatives (L = N -R-ATHs and N -H-ATH ) associated with the 1 H NMR analyses of the [Ag(L)] + complexes in polar and non-polar solvents revealed that the introduction of the N -substituent significantly enhanced the extractability of Ag +, due to the "hydrophobic cover" effect by the Ph–C–N framework in the [Ag( N -R-ATH )] + complexes.